Rekonstruksi Makna Tradisi Suroan Bagi Umat Islam di Petilasan Sri Aji Jayabaya Kabupaten Kediri - Ammar Kukuh Wicaksono; Nailal Muna (Realita : Jurnal Penelitian dan Kebudayaan Islam, 2022)
Suroan is a tradition that is commonly practiced by Javanese people, such as the Suroan tradition in Petilasan Sri Aji Jayabaya, the King of Kediri who is famous for the Jayabaya term. The suroan tradition has been passed down for a long time. The Qur'an is the holy book of Muslims which also talks about tradition, culture, and multiculturalism. This study uses a qualitative research method with a phenomenological approach that will examine the ritual process of one Suro at Petilasan Sri Aji Jayabaya with the approach of the Qur'an as the sacred text of Muslims. The results of the study stated that the suroan tradition is an acculturation of Islamic and Javanese culture. And culture is something that is allowed in the Koran as long as it does not conflict with divine values ​​and monotheism.